1995
DOI: 10.1016/0092-8674(95)90036-5
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin receptor ligation and activated rac uncap actin filament barbed ends through phosphoinositide synthesis in permeabilized human platelets

Abstract: Cells respond to diverse external stimuli by polymerizing cytoplasmic actin, and recent evidence indicates that GTPases can specify where this polymerization takes place. Actin assembly in stimulated blood platelets occurs where sequestered monomers add onto the fast-growing (barbed) ends of actin filaments (F-actin), which are capped in the resting cells. We report that D3 and D4 polyphosphoinositides, Pl(4)P, Pl(4,5)P2, Pl(3,4)P2, and Pl(3,4,5)P3, uncap F-actin in resting permeabilized platelets. The thrombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
529
0
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 640 publications
(547 citation statements)
references
References 43 publications
14
529
0
4
Order By: Relevance
“…Among them, polyphosphoinositides are known to play major roles in cellular signalling (reviewed in Payrastre et al, 2001). Small GTPases of the Rho family, RhoA and Rac, are now recognized to be regulators of PI4-P 5-kinase (Chong et al, 1994;Hartwig et al, 1995;Tolias et al, 1995Tolias et al, , 1998Tolias and Cantley, 1999). C3 from C. botulinum, which decreases Rho protein activity, also decreases the cellular level of PIP 2 (Payrastre et al, 2001).…”
Section: Toxins That Modulate Host Polyphosphoinositide Metabolismmentioning
confidence: 99%
“…Among them, polyphosphoinositides are known to play major roles in cellular signalling (reviewed in Payrastre et al, 2001). Small GTPases of the Rho family, RhoA and Rac, are now recognized to be regulators of PI4-P 5-kinase (Chong et al, 1994;Hartwig et al, 1995;Tolias et al, 1995Tolias et al, , 1998Tolias and Cantley, 1999). C3 from C. botulinum, which decreases Rho protein activity, also decreases the cellular level of PIP 2 (Payrastre et al, 2001).…”
Section: Toxins That Modulate Host Polyphosphoinositide Metabolismmentioning
confidence: 99%
“…It has been known for some time that integrins can stimulate the production of Phosphatidyl Inositol biphosphate (PIP 2 ) and recent studies have provided evidence that this e ect is mediated by Rho (Chong et al, 1994;Hartwig et al, 1995), possibly through its interaction with a type I isoform of phosphatidyl inositol 4-phosphate 5-kinase (PIP4-5K) (Ren et al, 1996). The increase in PIP 2 synthesis by Rho A is potentially relevant to focal adhesion assembly because the actin binding activity of several cytoskeletal proteins such as pro®lin and gelsolin is modulated by PIP 2 in vitro (Hartwig et al, 1995) and PIP 2 is enriched in focal adhesion plaques. In light of this, Gilmore and Burridge (1996) reported that the association of PIP 2 with vinculin induces a conformational change in vinculin, allowing it to interact with talin, which binds actin.…”
Section: Role Of Rho Family Of Proteins In Focal Adhesion Assemblymentioning
confidence: 99%
“…The activation of ERM proteins invariably requires PIP2 local accumulation (Hartwig et al 1995;Tolias et al 2000;Honda et al 1999). Two putative binding sites were identified, and PIP2 binding was demonstrated to be essential in guiding ezrin to cell surface locations (Barret et al 2000).…”
Section: Introductionmentioning
confidence: 99%